Research progress of immune checkpoint inhibitor related autoimmune hypophysitis - LI Jia-yi, XING Bing (Jichu yixue yu linchuang, 2020)
Immunotherapy induced hypophysitis (IH) has been demonstrated an autoimmune adverse effect of immune checkpoint inhibitors treatment of malignant tumors. The incidence of IH depends on types of immunotherapeutic agents. Patients with IH often present non-specific symptoms, ACTH, TSH and gonadotrophin deficiencies, and radiographic pituitary enlargement. Hormone replacement is recommended to be applied on IH patients. High-dose glucocorticoids but not supported by recent studies. This study systematically reviewed the prevalence, epidemiological characteristics, clinical characteristics, treatment and prognosis of IH.